First European Interlaboratory Ring Test Study to Detect DNA of Crayfish and the Crayfish Plague Pathogen From Water Samples - Bohman, Patrik; Andersson, Kristofer; Strand, David A.; Baudry, Thomas; Theissinger, Kathrin; Maguire, Ivana; Aluma, Michael; Aspán, Anna; Bláha, Martin; Bostjancic, Ljudevit Luka; Delaunay, Carine; Diéguez‐Uribeondo, Javier; et al. (John Wiley & Sons, 2026)
In recent years, European countries have intensified efforts to control or limit the spread of invasive freshwater crayfish and the crayfish plague pathogen Aphanomyces astaci, while working to conserve native species such as the noble crayfish (Astacus astacus). Although crayfish shed relatively low amounts of DNA into their environment, environmental DNA (eDNA) approaches have proven effective for detecting their presence. A range of protocols and equipment is currently used in eDNA-based monitoring of freshwater crayfish. To evaluate how methodological variation influences detection accuracy, we conducted the first European interlaboratory ring test using eDNA to detect A. astacus, the invasive signal crayfish Pacifastacus leniusculus, a chronic carrier of A. astaci, and the pathogen itself. The aim is to harmonize monitoring methods for crayfish and disease surveillance across laboratories. Eleven teams from thirteen European countries participated, each using its own equipment and protocols to collect and filter water from indoor tanks and outdoor ponds where the presence of A. astacus and P. leniusculus had been experimentally manipulated, as well as from a natural lake containing a P. leniusculus population. The resulting samples were analyzed in each team's laboratory. Despite methodological differences, all teams successfully detected DNA from both crayfish species in indoor tanks (3–10 crayfish/m3). However, detection accuracy declined in outdoor ponds where crayfish density was an order of magnitude lower (0.32 crayfish/m3). Detection was most variable for A. astaci, likely due to its very low prevalence in the host stock. Our study demonstrates the challenges of achieving consistent eDNA results across laboratories and highlights the importance of interlaboratory comparisons. It also underscores the need to identify sources of variability and error, an essential step toward developing robust and standardized protocols. This multinational intercalibration and exchange of knowledge improved methodology and enhanced reliability in crayfish detection.
Keywords: Aphanomyces astaci; Astacus astacus; eDNA; inter- calibration; Pacifastacus leniusculus; qPCR; standardization